Methods of Accelerated Prediction of The Shelf Life of Medical Polysaccharide-Based Hydrogels - Byrkina, T.S.; Loveckij, K.P.; Oltarzhevskaya, N.D. (Biomedical Chemistry: Research and Methods, 2018)
The paper describes an accelerated technique for determining the warranty period for the hydrogel-based polymer materials used for medical purposes. It deals with the technological production stages of hydrogel therapeutic materials “Kolegel” based on a polysaccharide of sodium alginate. On these stages deterioration of the material properties might lead to reduction of the shelf life of products (using natural raw materials, sterilization). The article introduces the ways to reduce this negative effect and subsequently increase the warranty period of the medical product by adding stabilizing additives into its composition. The method for determining the shelf life of sodium alginate hydrogel material depends on the added stabilizing additives (potassium sorbate and preservative based on 2-phenoxyethanol) in the “accelerated aging” mode; based on a mathematical description of two parallel processes occurring in hydrogels which are stored at elevated temperatures, namely: a change in the microbial contamination of hydrogels to the stage of final sterilization (using the Barany-Roberts model), a change in the dynamic viscosity after the conclusion of radiation sterilization of hydrogels (using a model based on the Arrhenius equation).